How we became human: mimetic theory and the science of evolutionary origins - Antonello, Pierpaolo; Gifford, Paul (Studies in Violence, Mimesis, and Culture, 2015)
Intro -- Contents -- Acknowledgments -- Introduction -- Part One. Questions of Methodology and Hermeneutics: Mimetic Theory, Darwinism, and Cultural Evolution -- Coevolution and Mimesis (William H. Durham) -- Genes and Mimesis: Structural Patterns in Darwinism and Mimetic Theory (Paul Dumouchel) -- Maladaptation, Counterintuitiveness, and Symbolism: The Challenge of Mimetic Theory to Evolutionary Thinking (Pierpaolo Antonello) -- Part Two. Imitation, Desire, Victimization: Examining Mimetic Theory on the Evidence -- Convergence between Mimetic Theory and Imitation Research (Scott Garrels) -- The Deepest Principle of Life: Neurobiology and the Psychology of Desire (William B. Hurlbut) -- The Three Rs: Retaliation, Revenge, and (Especially) Redirected Aggression (David P. Barash) -- Part Three. Violent Origins Revisited -- Violent Origins: Mimetic Rivalry in Darwinian Evolution (Melvin Konner) -- Mechanisms of Internal Cohesion: Scapegoating and Parochial Altruism (Zoey Reeve) -- A Mediatory Theory of Hominization (Giuseppe Fornari) -- Part Four. Interpreting Archaeological Data: Mimetic Readings of Çatalhöyük and Göbekli Tepe -- Animal Scapegoating at Çatalhöyük (René Girard) -- Self-transcendence and Tangled Hierarchies in Çatalhöyük (Jean-Pierre Dupuy) -- Rethinking the Neolithic Revolution: Symbolism and Sacrifice at Göbekli Tepe (Paul Gifford and Pierpaolo Antonello) -- Part Five. The Evolutionary Hermeneutics of Homo Religiosus -- Intrinsic or Situated Religiousness: A Girardian Solution (Warren S. Brown, James Van Slyke, and Scott Garrels) -- Homo religiosus in Mimetic Perspective: An Evolutionary Dialogue (Paul Gifford) -- About the Authors -- Index.